Enhanced Co₂ Adsorption Using Activated Carbon From Tea Stem Waste Via Activation–Carbonization Strategy - Supriadi, Edi; Efriyana Kampai; Muhdarina; Joni Prasetyo; Yessie Widya Sari; Tanti Ardiyati; Ary Mauliva Hada Putri (Jurnal Sains Materi Indonesia, 2026)
Tea stem agroindustrial waste, rich in cellulose, hemicellulose, and lignin, presents a promising low-cost precursor for sustainable activated carbon production. This study explores the activation–carbonization approach for synthesizing porous activated carbon and evaluates its effectiveness for CO₂ capture. Chemical activation was conducted using 60% w/v KOH at different activator-to-precursor ratios (0.5:1, 1:1, and 2:1 v/w), followed by carbonization at 250°C, 350°C, and 450°C in a fixed-bed pyrolysis reactor under nitrogen atmosphere. Among all samples, A1-450 0.5 (450°C, 0.5:1 ratio) exhibited the highest CO2 adsorption capacity (1.9500 mmol g⁻¹), attributed to its high surface area (679.4 m² g⁻¹) and predominantly microporous structure. XRD analysis confirmed the presence of disordered graphitic domains with broad peaks at 2θ = 22° and 44°, while FTIR revealed abundant surface functional groups (OH, C=C, CO) essential for CO2 interactions. SEM-EDX characterization showed a heterogeneous porous surface and high carbon content (78.23%). These findings demonstrate that the activation–carbonization route is more effective than carbonization–activation in producing high-performance bio-based CO₂ adsorbents, offering a viable strategy for valorizing agro-waste into functional carbon materials